Acquired nystagmus as the initial presenting sign of chiasmal glioma in young children. (November 2015) - Toledano, Helen; Muhsinoglu, Orkun; Luckman, Judith; Goldenberg-Cohen, Nitza; Michowiz, Shalom
Abstract Background/Purpose The aim of the study was to investigate the incidence of nystagmus at diagnosis in children with optic pathway glioma involving the chiasm and hypothalamus. Methods Twenty-two patients with a measurable optic pathway/hypothalamic glioma (without neurofibromatosis-1) were followed in our center from 2001 to 2013. The medical files were retrospectively reviewed for demographic and clinical findings, and the imaging scans, for tumor characteristics. Results There were 9 boys and 13 girls of mean age 3.5 ± 4.4 years at diagnosis; 15 were aged <2 years. Tumor size ranged from 10 × 6 mm to 62 × 29 mm. Mean duration of follow-up was 8.3 ± 5.4 years. Nystagmus was detected at diagnosis in 10 children (45%), all <2 years old (66.6% of the younger group); no child older than 2 years presented with nystagmus. Nystagmus, once present, did not resolve and continued throughout follow-up. There were no cases of new onset of nystagmus during follow-up in the children in whom it was not detected at diagnosis. Treatment consisted of partial resection/biopsy with/without shunting (n = 13) and chemotherapy (n = 19) with (n = 2) or without adjuvant radiation. Of the 22 children, 6 had a radiographic response to treatment, 8 remained stable, and 8 (all of whom received chemotherapy) showed disease progression despite treatment. Conclusion In conclusion, monocular nystagmus is a more common presenting sign of optic pathway/hypothalamic glioma in children <2 years old than previously estimated. Although subtle, nystagmus has a very narrow differential diagnosis, and its presence should raise suspicions of a chiasmal tumor with prompt referral for imaging. The visual prognosis is moderate to poor.